Aerobic exercise improves inflammation and insulin resistance in skeletal muscle by regulating miR-221-3p via JAK/STAT signaling pathway - Li, Nan; Zhang, Liang; Guo, Qiaofeng; Shi, Haiyan; Gan, Yanming; Wang, Weiqing; Yang, Xiaoying; Zhou, Yue (Frontiers in Physiology, 2025)
BackgroundExercise improves insulin sensitivity and lipid metabolism while the mechanisms remain unclear. MicroRNAs (miRNAs) have been linked to the development of type 2 diabetes mellitus (T2DM) and served as a potential therapeutic target. The study aimed to explore how aerobic exercise prevents chronic inflammation and insulin resistance (IR) in skeletal muscle.MethodsFifty C57BL/6J male mice were divided into a normal (CON) or high-fat diet (HFD) for 12 weeks, followed by treadmill training for 8 weeks. Glucose levels were evaluated by glucose tolerance test, insulin tolerance test and kits. Chronic inflammatory states were evaluated by enzyme-linked immunosorbent assay and immunofluorescence stain. The role of miR-221-3p was determined using miRNA sequencing and dual luciferase reporter gene assays. Metabolic alterations in skeletal muscle were investigated by Real-time PCR and Western blot.ResultsAerobic exercise reduced body weight, fasting blood glucose gain, and improved insulin sensitivity. It suppressed inflammation by altering IL-1β, IL-10 levels, and macrophage polarization in the skeletal muscle. Moreover, exercise prevented chronic inflammation by diminished miR-221-3p and downstream JAK/STAT pathways.ConclusionAerobic exercise improved chronic inflammation and IR in the skeletal muscle, with miR-221-3p as a key modulator of macrophage polarization.